Comparative metagenomics reveals alterations in the soil bacterial community driven by N-fertilizer and Amino 16® application in lettuce - Apostolos Kalivas (2018)
© 2017 Nutrients in the form of fertilizers and/or other additives such as amino acids, dramatically influence plant development and growth, plant nutrient composition and the level of soil pollution. Moreover, the treatment of soil microbiota is emerging as a new strategy in plant breeding to achieve desirable traits. Thus, integrated study of fertilizer application and soil microbiota might lead to a better understanding of soil-plant interactions and inform the design of novel ways to fertilize plants. Herein we report metagenomics data for soil microbiota in lettuce (Lactuca sativa) treated with fertilizer, amino acids or their combinations as follows: N-fertilizer + Amino16®, Amino16®, N-fertilizer and no treatment control. Data have been deposited in the NCBI Sequence Read Archive (SRA) (accession number: PRJNA388765).